Microencapsulation of extra-virgin olive oil by spray-drying: Influence of wall material and olive quality - Calvo, Patricia; Hernández, Teresa; Lozano, Mercedes; González-Gómez, David (European journal of lipid science and technology, 2010)
Encapsulation is a process by which small particles of core products are packaged within a wall material to form microcapsules. One common technique to produce encapsulated products is spray-drying which involves the conversion of liquid oils in the form of an emulsion into dry powders. Emulsification conditions, wall components, and spray-drying parameters have been optimized for the microencapsulation of different extra-virgin olive oils. To achieve this goal, the influences of emulsion conditions have been evaluated for different wall components such as proteins (sodium caseinate and gelatin), hydrocolloids (Arabic gum), and hydrolyzed starches (starch, lactose, and maltodextrin). In addition, for each of the tested conditions the ratio of wall solid-to-oil and spray-drying parameters were as well optimized.The microencapsulation effectiveness was determined based on process yield and the ratio between free and encapsulated oil (microencapsulation efficiency). Highest encapsulation yields were achieved when gelatin, Arabic gum and maltodextrin and sodium caseinate and maltodextrin were used as encapsulation agents and the ratio of wall solid-to-oil was 1:4 and 1:2, respectively. Under these conditions, 53% of oil was encapsulated. The influence of olive oil quality in the microencapsulation process was evaluated in terms of fatty acids profile alteration after the microencapsulation process.